2013
DOI: 10.14419/ijbr.v1i1.703
|View full text |Cite
|
Sign up to set email alerts
|

Reduced glutathione and acetylcholinesterase expressions in Perna indica exposed to trivalent arsenic

Abstract: In the present study Indian brown mussel, Perna indica was exposed to 20, 40, 80, 160 and 320 ppb (µg/l) arsenic concentrations under short-term chronic toxicity bioassay (14 days) for the assessment of reduced glutathione and acetylcholinesterase as potential biochemical biomarkers in arsenic pollution. A higher level of reduced glutathione (GSH) and increased acetylcholinesterase (AchE) activity was expressed when compared to control in 160 and 320 ppb arsenic concentration. The found values were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Although in recent years the number of studies that investigated the interactions between ChE and NMs have been increasing, generally demonstrating an inhibition of their activity in invertebrates as a consequence of CNTs exposure (De Marchi et al 2017a;Monserrat et al 2017;De Marchi et al 2018a;, opposite results were observed in the present study, showing no inhibition of AChE activity in exposed organisms under both materials and both salinities. Such result may be related to the fact that organisms try to reduce neurotransmitter excess in the synaptic clefts, which was already showed in the bivalve Perna indica exposed to arsenic (As) (Rajkumar, 2013). II) Alteration induced by salinity shifts modifying the sensitivity of the polychaetes and the toxicity of the CNTs was also observed in the present study.…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…Although in recent years the number of studies that investigated the interactions between ChE and NMs have been increasing, generally demonstrating an inhibition of their activity in invertebrates as a consequence of CNTs exposure (De Marchi et al 2017a;Monserrat et al 2017;De Marchi et al 2018a;, opposite results were observed in the present study, showing no inhibition of AChE activity in exposed organisms under both materials and both salinities. Such result may be related to the fact that organisms try to reduce neurotransmitter excess in the synaptic clefts, which was already showed in the bivalve Perna indica exposed to arsenic (As) (Rajkumar, 2013). II) Alteration induced by salinity shifts modifying the sensitivity of the polychaetes and the toxicity of the CNTs was also observed in the present study.…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…In what regards to the neurotoxic impacts, both conditions A and a inhibited AChE activity, with higher injuries when organisms were exposed to the highest As concentration (contaminated seawater). Rajkumar (2013) also showed that As concentrations (80 µg/L) induced neurotoxicity in mussels. A similar pattern was shown by other authors with clams (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…Table 1 shows any significant differences of the average difference of physicochemical properties and nutrient salts dissolved of seawater before and after the tests. Besides, the effects of the variation of the abiotic parameters have been reported on CAT activity and bioaccumulation of heavy metals [12,[22][23][24][25][26]. Moreover, temperature and salinity affected the filtration rate of mussels and the amount of oxygen consumed.…”
Section: Some Physicochemical Properties and Nutrient Saltsmentioning
confidence: 99%
“…indicates that the total level of protein had variation with no linearity in the Cd, Pb, and Cu treated P. perna. Protein reserves appear to be affected by the chemical pollutant [25,26]. However, Rajkumar (2013) [26] reported that the metabolites of mussels given by the level of total protein can be affected by heavy metal exposures.…”
Section: Tissue Metal Contentmentioning
confidence: 99%